Stephen Hawking, contributions of an influential physicist - Castro Ponce, Mario (Razón y fe, 2021)
On March 14, 2018, Stephen W. Hawking, one of the most admired scientists of recent times, died at the age of 76, both for his academic contributions to physics and for his ability to disseminate issues of great theoretical complexity to the general public. So much so that his work A Brief History of Time has become a world bestseller. Behind the most widespread image of a media figure who was diagnosed with ALS at the age of 21 and for quite some time had been practically immobilized, is a great researcher and scientific disseminator, which has earned him important awards around the world. But what are his most relevant contributions to science and, in particular, to physics? This is the purpose of this paper.
Keywords: physics; origin of the universe; black holes